Incentive Contracts for Environmental Services and Their Potential in REDD - Fortmann, Lea; Cordero, Paula; Sohngen, Brent; Roe, Brian (World Bank, Washington, DC, 2014)
Implementation arrangements for Reducing Greenhouse Gas Emissions from Deforestation and Forest Degradation can be seen as contracts that could address some of the inherent problems with forest carbon credits that often lead to high transaction costs -- measuring, monitoring, and verification. Self-enforcing contracts, where it is in the best interest of the environmental service providers to comply with the contracts, may be one way to reduce these costs if providers have incentives to uphold their end of the contract. While the literature on Reducing Greenhouse Gas Emissions from Deforestation and Forest Degradation is extensive, there is little information available to guide policy makers or investors on what form such contracts should take. After providing an overview of the current status of Reducing Greenhouse Gas Emissions from Deforestation and Forest Degradation and its role as a tool for reducing carbon emissions on an international scale, the paper describes key issues regarding implementation and reviews the literature on contracts from the related area of Payments for Ecosystem Services programs, which face similar challenges. The remainder of the paper reviews various contractual mechanisms from agricultural and forestry related projects that have been proposed or are being used in practice and discusses the various implications associated with their design and implementation.